Using affective judgement to increase physical activity in British adults. (27th February 2017) - Forster, Alice S; Buykx, Penny; Martin, Neil; Sadler, Susannah; Southgate, Ben; Rockliffe, Lauren; Walker, Ian
Summary: Mobile phone apps have been shown to increase physical activity (PA), but existing apps fail to target the emotional aspects of PA, which influence whether individuals are active. We developed an app that encourages individuals to focus on the emotional aspects of PA. We aimed to assess the acceptability of this app, and conduct a preliminary evaluation of efficacy. The app was developed in collaboration with users through focus groups. Seven users tested the app over 4 months and provided feedback on acceptability, aesthetics and functionality in a follow-up focus group. Results were summarized descriptively. Before testing the app, participants completed a questionnaire assessing their current PA and psychological antecedents of PA. A second questionnaire was completed at the follow-up focus group. Change scores are reported for each participant and overall. The social and reminder aspects facilitated motivation to be active and many found it easy to integrate into their lives. Most suggested modifications. Small improvements in number of minutes spent walking per week were observed (overall mean change +25 min) and some psychological antecedents of PA (overall mean change for social support for PA +0.14, self-efficacy for PA +0.17, outcome expectations about PA +0.20; all five-point scales), but reductions were seen in other domains. The app was acceptable to users, although developments are required. Testing with a small number of individuals, offering preliminary evidence of efficacy of this app, provides justification for further evaluation on a larger scale.